IGF2 deficiency causes mitochondrial defects in skeletal muscle. Issue 7 (16th April 2021) - Zhu, Yiyi; Gui, Weiwei; Tan, Bowen; Du, Ying; Zhou, Jiaqiang; Wu, Fang; Li, Hong; Lin, Xihua
Abstract: Exercise training improves muscle fitness in many aspects, including induction of mitochondrial biogenesis and maintenance of mitochondrial dynamics. The insulin-like growth factors were recently proposed as key regulators of myogenic factors to regulate muscle development. The present study aimed to investigate the physical exercise impact on insulin-like growth factor 2 (IGF2) and analyzed its functions on skeletal muscle cells in vitro . Using online databases, we stated that IGF2 was relatively highly expressed in skeletal muscle cells and increased after exercise training. Then, IGF2 deficiency in myotubes from C2C12 and primary skeletal muscle cells (PMSCs) led to impaired mitochondrial function, reduced mitochondria-related protein content, and decreased mitochondrial biogenesis. Furthermore, we explored the possible regulatory pathway and found that mitochondrial regulation in skeletal muscle cells might occur through IGF2-Sirtuin 1 (SIRT1)-peroxisome proliferator-activated receptor-γ co-activator-1α (PGC1α) signaling pathway. Therefore, the present study first demonstrated the relationship between IGF2 and mitochondria in skeletal muscle.